Getting the state out of pre-school & childcare: Ending the nannying of UK parents - Ryan Bourne; J. R. Shackleton (Institute of Economic Affairs (IEA), 2017)
Decisions on childcare arrangements were largely a private matter until the 1990s. A political consensus has since arisen that government action is needed to raise the quality of provision, to make it more affordable and to support parental labour market attachment. Childcare and pre-school policy is accordingly a fast-growing area of state intervention. The UK now spends more than 7 billion of taxpayers' money per year on these areas, and heavily regulates the childcare sector. Government directly provides childcare, gives financial support (via a 'free' hours entitlement, the tax credit system and the forthcoming 'tax-free childcare') and closely regulates the sector (determining staff-child ratios, qualifications and training requirements, and the Ofsted inspection regime). It makes other interventions through Children's Centres, aimed at disadvantaged children and their families. The growing state involvement has been associated with childcare that is expensive by international standards, with high out-of-pocket costs to parents despite increasing levels of state subsidy. Many lower-cost providers such as childminders have been driven out of the sector. Childcare subsidies have a significant displacement effect on private sector activity. There is only limited evidence that they increase female labour force participation - and any increases come at a high budgetary cost. Nor do most interventions seem to lead to lasting improvements in child development. There is also a disconnect between parents' preferences and the prescriptions of experts. Analyses claiming 'market failures' in childcare are weak: they assume that government has the knowledge and ability to perfectly account for all external effects. Arguments that we should subsidise childcare to maximise parents' economic contribution confuse recorded GDP with general economic welfare. Government subsidy and regulation of childcare and pre-school is a 'feel-good' policy which it is difficult to challenge or question. But it should be fundamentally reassessed, under the guiding principle of allowing parents to make free choices about the types and quality of provision they want for their children. Regulation of the childcare and pre-school sector should be scaled back - creating a competitive environment in which costs would fall while government regulation would be replaced by private forms of quality assurance. Universal free care should be scrapped, along with 'tax-free' childcare and the Early Years Foundations Stage. Any state intervention should be targeted towards poorer families with low levels of labour market attachment, rather than (as often at present) having perverse re-distributional consequences. Some groups do badly out of government intervention: there is a hidden ethnic dimension as some minority groups do not make much use of formal childcare, while others have been squeezed out of work as childminders by excessive regulation. Failure to change course risks beneficiaries of childcare subsidies - both providers and consumers - becoming entrenched interest groups, continually demanding more taxpayer money for confused and uncertain outcomes.
Keywords: H53; I38; H11; H53; I38; H11; 330